1945
DOI: 10.1111/j.1748-1716.1945.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidation of Body Fat in Vitamin E Deflciency

Abstract: Summary. Chicks fed vitamin E deficient diets containing 5 per cent cod liver oil developed peroxides in the adipose tissue during the period in which the known symptoms of exudation, and particularly brown coloration of the same tissue occurred. The relation between the peroxidation and the symptoms is discussed. Subcutaneous injection of 0.3 ml of cod liver oil with a peroxide value of 16 to chicks receiving a normal diet, resulted in very marked peroxidation at the site of injection accompanied by a progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1946
1946
1989
1989

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Examination of embryos from GSHpx activity, no effect on the incidence hens fed the basal diet, that died between of exudative diathesis would be expected. day 18 and day 21 of incubation, revealed Experiment 2 was conducted to evaluate that approximately 25% showed symptoms the effect of selenium supplementation on resembling the classical signs of exudative diathesis in growing chicks, as described by Dam and Glavind (1938) and Dam and Granados (1945). Furthermore, approximately 50% of the newly-hatched chicks showed signs of the deficiency disease.…”
Section: Results From Experiments Ib Presented Inmentioning
confidence: 98%
“…Examination of embryos from GSHpx activity, no effect on the incidence hens fed the basal diet, that died between of exudative diathesis would be expected. day 18 and day 21 of incubation, revealed Experiment 2 was conducted to evaluate that approximately 25% showed symptoms the effect of selenium supplementation on resembling the classical signs of exudative diathesis in growing chicks, as described by Dam and Glavind (1938) and Dam and Granados (1945). Furthermore, approximately 50% of the newly-hatched chicks showed signs of the deficiency disease.…”
Section: Results From Experiments Ib Presented Inmentioning
confidence: 98%
“…Thus Dam,Kruse,Prange & Ssndergaard (195 I ) found that methylene blue, thionine, thiodiphenylamine, tetraethyl thiuram disulphide (Antabuse), nordihydroguiaretic acid and ascorbic acid could all afford considerable, but incomplete, protection against the effects of vitamin E deficiency in chicks. Dam & Granados (1952) found that methylene blue could even prevent resorptions in rats. Moore, Sharman & Ward (1953a,b,c, 1954 failed to confirm this last finding.…”
Section: Selenium and Vitamin E In Nutritionmentioning
confidence: 99%
“…T h e incisor teeth of rats lost their normal brown pigmentation (Moore, 1943). In rats given cod-liver oil, but not dosed with vitamin E, the fat depots became brown and peroxides were present (Dam & Granados, 1945). Red blood cells taken from rats deficient in vitamin E were found to be rapidly haemolysed in the presence of dialuric acid (Gyorgy & Rose, 1948 One further lesion in the rat deserves our special attention in view of its importance in studies of Se-vitamin E interrelationships.…”
mentioning
confidence: 99%
“…However, with the possible exception of adipose tissue (Dam and Granados, 1945), no increase in tissue peroxides could be detected in experimental animals made vitamin E deficient (Dam, 1962;Bunyan et a/., 1967). However, with the possible exception of adipose tissue (Dam and Granados, 1945), no increase in tissue peroxides could be detected in experimental animals made vitamin E deficient (Dam, 1962;Bunyan et a/., 1967).…”
Section: Vitamin E As a Biological Antioxidantmentioning
confidence: 90%